SLOW FACIAL SIGNS AND THEIR PSYCHODIAGNOSTIC VALUE - Біда, Сергій Олександрович; Луценко, Олена Львівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2019)
The current study is devoted to the identifiation of the scientifi basis of permanent facial expression as a psychodiagnotic measure. The aim of the research is to investigate relationships between slow facial signs (SFS) and emotional personality traits with taking into account age and gender on the sample ofEastern Ukrainians (201 participants). To that end, we measured participants’ personality traits levels and photographed their neutral faces in order to identify any SFS on the photographs of their faces. The test battery included the Spielberger state-trait anxiety inventory, Taylor manifest anxiety scale, Buss Durkey hostility inventory, Vasserman social frustration questionnaire, Vasserman neuroticism scale, Personal differential inventory, “Draw-A-Person” and “Draw-A-Person-In-The-Rain” projective tests. We applied Facial Action Coding System (Ekman, Friesen, & Hager) to identify and interprete SFS on the photographs. We found that the most part of revealed SFS relates to anger (12) and sadness (11). The fewest number of revealed SFSrelates to disgust / contempt (5), fear (4) and happiness (4). The elder a person becomes the more increasing number of SFS of sadness (highest rates), anger (lower rates), fear (still lower) and happiness (lowest rates) is expected in one’s face. There are no signifiant differences in manifesting SFS between men and women. We found signifiant correlations between relevant SFS and traits anxiety, depression, and agressiveness (in itsguilt and resentment aspects).